Faktor-Faktor Yang Mempengaruhi Tax Avoidance Dengan Kepemilikan Manajerial Sebagai Pemoderasi Pada Perusahaan Pertambangan Di Bursa Efek Indonesia (BEI) Periode 2015-2019 - Alya Zulfa Cahyani; Syahril Djaddang; Mombang Sihite; Yayan Hendayana (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study examines the effect of thin capitalization, capital intensity, and fiscal loss compensation on tax avoidance and to examine managerial ownership in moderating the effect of thin capitalization on tax avoidance in mining sector companies listed on the indonesia stock exchange in 2015-2019. This study uses a sample of 35 mining sector companies listed on the indonesia stock exchange for the 2015-2019 period with the sampling technique using the purposive sampling method and the research data using secondary data. Methods data analysis uses moderated regression analysis (mra) with spss 25.0 software. The results of this study indicate that thin capitalization has a positive and significant effect on tax avoidance, while capital intensity has a negative and significant effect on tax avoidance and fiscal loss compensation has no effect on tax avoidance and managerial ownership weakens the effect of thin capitalization on tax avoidance. The control variable, namely roa, has a negative and significant effect on tax avoidance and company size has no effect on tax avoidance.